Changes in the growth performance, serum biochemistry, rumen fermentation, rumen microbiota community, and intestinal development in weaned goats during rumen-protected methionine treatment - Wang, Youli; Liu, Wei; Li, An; Qubi, Wuqie; Gong, Chengsi; Li, Xuening; Xing, Jiani; Shi, Haitao; Li, Yanyan; Wang, Yong; Lin, Yaqiu (Frontiers in Veterinary Science, 2024)
Rumen-protected methionine (RPM) such as coated methionine (CM) and 2-hydroxy-4-(methylthio)-butanoic acid isopropyl ester (HMBi) was usually used in dairy cows, but how RPM affects meat goats remains unclear. In this study, thirty weaned male Jianzhou Da’er goats were randomly assigned to one of three treatments: fed basal diet or basal diet supplemented with 0.12% CM or 0.22% HMBi, with the aim of examining their impact on growth performance, serum biochemistry, rumen fermentation, rumen microbiota, and intestinal development in meat goats. The findings indicate that HMBi supplementation led to an increase in body weight, feed intake, and feed-to-gain ratio, whereas CM only resulted in an increase in feed intake (all p < 0.05). Both CM and HMBi resulted in an increase in serum total cholesterol (TC), blood urea nitrogen (BUN), alkaline phosphatase (ALP), and aspartate aminotransferase (AST), albeit with a decrease in serum triglycerides (TG) and β-hydroxybutyric acid (BHB, all p < 0.05). Both CM and HMBi supplementation decreased the rumen butyric acid concentration (both p < 0.05). The 16S rRNA sequencing showed that HMBi supplementation significantly increased the total abundance of Bacteroidetes and Firmicutes. Both CM and HMBi supplements increased the abundance of Rikenella and Proteiniphilum but decreased the abundance of Eisenbergiella, Enterocloster, Massilioclostridium, Eubacterium, Angelakisella, Blastopirellula, Christensenella, and Pseudoruminococcus. CM supplementation specifically increased the abundance of Desulfobulbus, Sodaliphilus, and Coprococcus while decreasing the prevalence of Anaerocella, Mogibacterium, and Collinsella. The supplementation of HMBi significantly enhanced the abundance of Paraprevotella, Bacilliculturomica, Lachnoclostridium, Dysosmobacter, Barnesiella, and Paludibacter, while decreasing the abundance of Butyrivibrio and Pirellula. Moreover, the administration of both CM and HMBi supplementation resulted in an increase in the ammonia-producing and sulfate-reducing bacteria, whereas a decrease was observed in the ammonia-oxidating, health-associated, and disease-associated bacteria. Correlational analysis revealed that TG and BHB had a positive correlation with disease-associated and ammonia-oxidating bacteria, whereas they had a negative correlation with ammonia-producing bacteria. The serum BUN, ALP, and AST were positively correlated with ammonia-producing bacteria but were negatively correlated with ammonia-oxidating bacteria. Furthermore, both CM and HMBi supplementation improve the development of the small intestine, with HMBi having a better effect. In summary, this study indicates that both CM and HMBi supplementation improve lipid metabolism, nitrogen utilization, and intestinal development. The growth promotion effect of HMBi supplementation may be attributed to the increased abundance of volatile fatty acid-producing and nitrogen-utilizing bacteria and improved intestinal development.